Analysis The Impact of Government Proliferantion on Educational and Economic - Husna, Dalila; Rumayya, Rumayya (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2021)
The government proliferantion in Indonesia become a consequence of the existence of a policy of fiscal desentalisasi. The existence of the government proliferantion is expected to shorten the span of control so that the goal of improving the well-being of society and the public service can be achieved. This study goals to analyze the impact of the government proliferantion on the regional educational and economic outcomes against on 491 Kabupaten/Kota in Indonesia. This research uses the Difference in Difference as a tool of analysis. Data obtained from the Indodapoer-World Bank year 2001 until 2014. The impact of the presence of the government proliferantion against outcomes education is lowering the level of literacy through a decrease in the number of buildings on the SD output though it is insignificant and its impact on economic outcomes effect increasing income per capita community that in proxy through household spending per capita and GDP per capita, increasing the number of workers, and lower levels of poverty through increased output in the electricity, road access to the village dirt road, and the village gravel road. The impact in General of the expansion area is a local Government has succeeded in transferring funds to the poor but not with a business climate that is shown by the results of the constant price GDP as a whole which indicates significant results negative. Keywords: Government Proliferantion, Difference in Difference, Educational, Economic.JEL : R1, H00, I21, I25